The CALS Lens: Optical and Perceptual Considerations in Aspheric Topography - Evans, Thomas C (Canadian Journal of Optometry, 1983)
When aspheric surfaces are applied to the eye in the form of contact lenses, both optical and perceptual factors must be considered in vivo. Various clinical and theoretical articles are reviewed and limits established for perceptual factors such as tolerance to retinal defocus in the normally aberrated eye. The range of asphericity (k) and eccentricity (e) required to optically correct for presbyopia and astigmatism is predicted for given pupillary radii. The topography of the CALS aspheric front surface is shown to be within the predicted range. Several factors of fitting and lens design are discussed with respect to a previous clinical study of the CALS soft lens.